Państwowe przedsiębiorstwo pocztowe, telegraficzne i telefoniczne w II Rzeczypospolitej - Sobień, Karol (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
The article presents an analysis of one of the main companies in pre-war Poland. The author describes how the activities of postal, telegraph and telephone services were organized and the importance of state telecommunications company for organizing social and economic life, particularly through monolithic approach to distribution of information in Poland. This is followed by description of commercialization of the company and its further development, particularly during the Great Depression.